Rapid and sensitive detection of Feline immunodeficiency virus using an insulated isothermal PCR-based assay with a point-of-need PCR detection platform. (July 2015) - Wilkes, Rebecca Penrose; Kania, Stephen A.; Tsai, Yun-Long; Lee, Pei-Yu Alison; Chang, Hsiu-Hui; Ma, Li-Juan; Chang, Hsiao-Fen Grace; Wang, Hwa-Tang Thomas
Feline immunodeficiency virus (FIV) is an important infectious agent of cats. Clinical syndromes resulting from FIV infection include immunodeficiency, opportunistic infections, and neoplasia. In our study, a 5′ long terminal repeat/ gag region–based reverse transcription insulated isothermal polymerase chain reaction (RT-iiPCR) was developed to amplify all known FIV strains to facilitate point-of-need FIV diagnosis. The RT-iiPCR method was applied in a point-of-need PCR detection platform—a field-deployable device capable of generating automatically interpreted RT-iiPCR results from nucleic acids within 1 hr. Limit of detection 95% of FIV RT-iiPCR was calculated to be 95 copies standard in vitro transcription RNA per reaction. Endpoint dilution studies with serial dilutions of an ATCC FIV type strain showed that the sensitivity of lyophilized FIV RT-iiPCR reagent was comparable to that of a reference nested PCR. The established reaction did not amplify any nontargeted feline pathogens, including Felid herpesvirus 1, feline coronavirus, Feline calicivirus, Feline leukemia virus, Mycoplasma haemofelis, and Chlamydophila felis . Based on analysis of 76 clinical samples (including blood and bone marrow) with the FIV RT-iiPCR, test sensitivity was 97.78% (44/45), specificity was 100.00% (31/31), and agreement was 98.65% (75/76), determined against a reference nested-PCR assay. A kappa value of 0.97 indicated excellent correlation between these 2 methods. The lyophilized FIV RT-iiPCR reagent, deployed on a user-friendly portable device, has potential utility for rapid and easy point-of-need detection of FIV in cats.